Quality and postharvest conservation of sour passion fruit genotypes - Araújo, James Maciel de; Andrade Neto, Romeu de Carvalho; Tavella, Leonardo Barreto; Leite, Hugo Mota Ferreira; Araújo, Marlon Lima de; Saraíva Lessa, Lauro; Abreu, Marcos Giovane Pedroza de; Sebim Marim, João Paulo (Comunicata Scientiae, 2024)
The postharvest phase is a limiting factor for climacteric fruits such as passion fruit due to rapid deterioration causing wilting and favoring the occurrence of pathogenic microorganisms. From this perspective, this study aimed to evaluate the postharvest quality of passion fruit genotypes cultivated in Mâncio Lima, Acre, as a function of the storage period after harvest. The experiment was set up and conducted at the Plant Science Laboratory of the Federal University of Acre, Campus Floresta. The experimental design was in randomized blocks, in a 10 x 5 factorial arrangement referring to 10 sour passion fruit genotypes and five postharvest evaluation periods, with three replications of six fruits. The fruits were evaluated for physical and chemical quality. Analysis of variance and polynomial regression were performed at 5% significance. The genotypes showed oscillations regarding the physical and chemical characteristics of the fruits depending on the storage time. All evaluated genotypes are recommended for cultivation. However, when harvested directly from the ground after detached from the plant, fruits must be stored for up to 10 days at room temperature.